RELACIÓN ENTRE LA EROSIÓN DENTAL Y LA MEDICACIÓN PARA EL ASMA EN NIÑOS: UNA REVISIÓN SISTEMÁTICA - Díaz Quevedo, André Alexis (2025)
Introduction: Dental erosion is an alteration that affects the integrity of teeth, which has several aetiologies. It is mentioned that asthma medications may be an etiologic factor; however, studies fail to clarify the possible association between these variables in children with asthma. Therefore, the purpose of this study will be to determine the relationship between dental erosion and asthma medication consumption in paediatric patients. Materials and methods: A systematic research was performed in databases such as MEDLINE (PubMed), Scopus, Web of Science, Scielo, Cochrane Library, Embase, LILACS and gray literature (Open Gray). Two researchers independently selected the articles according to the population, exposure, outcome, study design (PEOS) question using the Rayyan program. Newcastle-Ottawa scale was used to assess the risk of bias. Results: Six articles were included from 120 selected articles. The studies by Bairappan, Domenzain and Arafa studies show a higher prevalence of dental erosion in children with asthma medication as opposed to healthy children, whereas the studies by Dugmore and Rock, Alazmah and Rezende report a higher prevalence of erosive lesions in healthy children. Conclusions: Asthma medications are not a determining factor for the occurrence of erosive lesions in the teeth of paediatric patients with this systemic condition.